Effect of the Ordovician paleogeography on the (in)stability of the climate - A. Pohl; Y. Donnadieu; G. Le Hir; J.-F. Buoncristiani; E. Vennin (Climate of the Past, 2014)
The Ordovician Period (485–443 Ma) is characterized by abundant evidence for continental-sized ice sheets. Modeling studies published so far require a sharp CO2 drawdown to initiate this glaciation. They mostly used non-dynamic slab mixed-layer ocean models. Here, we use a general circulation model with coupled components for ocean, atmosphere, and sea ice to examine the response of Ordovician climate to changes in CO2 and paleogeography. We conduct experiments for a wide range of CO2 (from 16 to 2 times the preindustrial atmospheric CO2 level (PAL)) and for two continental configurations (at 470 and at 450 Ma) mimicking the Middle and the Late Ordovician conditions. We find that the temperature-CO2 relationship is highly non-linear when ocean dynamics are taken into account. Two climatic modes are simulated as radiative forcing decreases. For high CO2 concentrations (≥ 12 PAL at 470 Ma and ≥ 8 PAL at 450 Ma), a relative hot climate with no sea ice characterizes the warm mode. When CO2 is decreased to 8 PAL and 6 PAL at 470 and 450 Ma, a tipping point is crossed and climate abruptly enters a runaway icehouse leading to a cold mode marked by the extension of the sea ice cover down to the mid-latitudes. At 450 Ma, the transition from the warm to the cold mode is reached for a decrease in atmospheric CO2 from 8 to 6 PAL and induces a ~9 °C global cooling. We show that the tipping point is due to the existence of a 95% oceanic Northern Hemisphere, which in turn induces a minimum in oceanic heat transport located around 40° N. The latter allows sea ice to stabilize at these latitudes, explaining the potential existence of the warm and of the cold climatic modes. This major climatic instability potentially brings a new explanation to the sudden Late Ordovician Hirnantian glacial pulse that does not require any large CO2 drawdown.